2019
DOI: 10.1177/1363461518822407
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Cultural Formulation Interview: Findings and Implications for Revising the Outline for Cultural Formulation

Abstract: The DSM-IV Outline for Cultural Formulation (OCF) was a framework for assessment based on principles of cultural psychiatry. The Cultural Formulation Interview (CFI) for DSM-5 provided a tool enabling wider use of cultural formulation in clinical cultural assessment. Validation to justify the inclusion of the CFI in DSM-5 involved quantitative analysis of debriefing interviews of patients and clinicians for feasibility, acceptability and clinical utility. We now further examine qualitative field trial data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Three studies reported on the perspectives of family members who accompanied patients (Hinton et al., 2015; Paralikar et al., 2015, 2020). The first of these (Hinton et al., 2015) explored perceptions of the CFI’s feasibility, acceptability, and clinical utility from patient companions in India, Kenya, and the Netherlands during the pilot field trial, and found that they rated the CFI positively on all three domains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported on the perspectives of family members who accompanied patients (Hinton et al., 2015; Paralikar et al., 2015, 2020). The first of these (Hinton et al., 2015) explored perceptions of the CFI’s feasibility, acceptability, and clinical utility from patient companions in India, Kenya, and the Netherlands during the pilot field trial, and found that they rated the CFI positively on all three domains.…”
Section: Resultsmentioning
confidence: 99%
“…A study from an Indian field trial site found that patients with common mental disorders rated the CFI’s acceptability and clinical utility higher than did patients with psychosis and clinicians; in fact, patients with psychosis rated acceptability and clinical utility lower than patients without psychosis and clinicians (Paralikar et al., 2015). Another Indian study by the same research team used qualitative analyses of patient and clinician debriefing interviews from the field trial to propose revisions to the OCF that situated narratives within social, political, and economic contexts (Paralikar et al., 2020). A study from the Dutch field trial site found slightly lower ratings of feasibility, acceptability, and clinical utility relative to the mean values of the overall field trial, though still in the positive range (Rohlof et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the process of conducting the CFI is as important as the content elicited. Research with the CFI has shown that patients value the ability of the clinician to express caring and concern through the CFI questions, which can enhance rapport and communication (Aggarwal, DeSilva, Nicasio, Boiler, & Lewis-Fernández, 2015; Paralikar, Deshmukh, & Weiss, 2020). By giving explicit attention to patients’ experience of suffering, and eliciting relevant aspects of their identity, understandings of illness, and current predicament, the use of the CFI conveys the clinician’s interest in the patient as a person.…”
Section: Disrupting and Transforming Current Psychiatric Assessment Mmentioning
confidence: 99%
“…In many high-resource settings, incorporation of the CFI into electronic health records (EHR) is a possible solution, especially if this can be organized in a way that guides overall case formulation and treatment planning. Several formats are in development, including the one suggested by Paralikar and colleagues (2020) based on the five domains of a revised OCF. However, the information documented in records is often limited and cannot capture the rich discussions and multiple perspectives presented in clinical team rounds and interdisciplinary case conferences.…”
Section: Identifying Effective Dissemination and Implementation Stratmentioning
confidence: 99%
See 1 more Smart Citation